Directive Speech Acts of Female Teachers in Learning and Teaching Interactions in Indonesian Language at Sman Nino Conis Santana Gleno, Ermera - Dirce Soares Babo; Siti Ainim Liusti; Ngusman Ngusman; Tressyalina Tressyalina (Riviera Publishing, 2026)
This study aims to describe the forms and functions of directive speech acts used by female teachers in Bahasa Indonesia teaching and learning interactions at SMAN Nino Conis Santana Gleno, Ermera. This research employs a qualitative approach with a descriptive method. The research data consisted of directive speech acts by female teachers, obtained through recording and observation techniques. The sources of data were three female Bahasa Indonesia teachers teaching class XII. The findings revealed 76 instances of directive speech acts used by female teachers in various forms and functions. The identified forms of directive speech include commanding, requesting, advising, inviting, and prohibiting. The functions of directive speech acts include directing students during the learning process, motivating students, managing the classroom, and evaluating students’ understanding. The most dominant types of directive speech acts are those of commanding and requesting, which primarily function to guide student learning activities.